Intensity Analysis of Gadget Use on Learning Disciplines of Elementary School Age Children - Arifin, Moch. Bahak Udin By; Marnah, Marnah (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2023)
The gadget is a technology with interesting features and applications so its use is very high. The use of gadgets is not only among adults but also among students. The use of gadgets that parents do not give limits and attention to will have a negative impact on students. This research aims to determine the intensity of using gadgets in the learning discipline of elementary school-age children. The research method used is descriptive qualitative. The data source used in this research is article documents obtained from Publis or Perish as primary data. At the same time, secondary data was obtained from cluster analysis and analysis graphs in research data collection techniques using Publis or Perish and Vos Viewer. The research data analysis technique uses the Milles and Huberman model, which consists of several stages: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the high intensity of using gadgets can hurt students. When students are already addicted to gadgets, they are likely to become dissidents, ignore the assignments given by the teacher, and become lazy to do practical activities. The impact is physical changes in students, decreased learning discipline, lack of interest in learning, disturbed learning concentration, and children becoming anti-social. At the same time, the positive impact is obtaining information without any restrictions and increasing friendship networks on social media.